THE EFFECT OF COOPERATIVE LEARNING MODEL OF THINK PAIR SHARE BASED ON CONCEPT MAPPING TOWARDS CIVICS ACHIEVEMENT - Ni Wayan Suyatni; Ndara Tanggu Rendra; Ni Wayan Rati (Journal of Psychology and Instruction, 2018)
This study is aimed at investigating the difference of students’ civics achievement between those who are taught by Think Pair Share model based on concept mapping and those who are taught by conventional learning model of the fifth grade students in Elementary School of Cluster I in Petang District. It is a quasi-experimental research using non-equivalent post-test only control group design. The population of this research is 102 students in grade V in Elementary School of Cluster I Petang District. The samples of this research are fifth grade students of SD Negeri 3 Carangsari as experimental group and fifth grade students of SD Negeri 1 Carangsari as control group. The data of civics achievement were collected by using multiple choice tests. The data obtained were analyzed using descriptive statistics and inferential statistical analysis (t-test). The result showed that tcount= 3,83 and ttable = 2,03 (tcount>ttable) which can be concluded that there are significant difference between the students’ civics achievement between those who were taught by Think Pair Share learning model based on concept mapping and those who were taught by the conventional learning model in grade V in Elementary School of Cluster I Petang District of Badung Regency in academic year 2017/2018.